Process over product: The 1990s United States hardcore and emo subcultures and DIY consumerism. (1st June 2018) - Sklar, Monica; Donahue, Mary Kate
This research focuses on the hardcore punk scene in the mid-1990s' United States and its clothing consumption experiences. Within the fashion cycle, various subcultures often consume and produce products in unique manners and timeframes and with assorted motives. Although many subcultures use a centralized retail space for scene development, hardcore did not; rather it produced and consumed the style utilizing the concepts of do-it-yourself (DIY) and bricolage. Qualitative mixed methods of data collection included literature research, social media discussions, open-ended survey participation, interviews and location visits. The results obtained indicate that for this subcultural community, the process to produce and consume was an integral part of meaning being imbued in the products.